On θ-b-Irresolute Functions - Rajesh, N. (Sarajevo Journal of Mathematics, 2024)
The concept of b-open sets was introduced by Andrijevic. The aim of this paper is to introduce and characterize θ-b-irresolute functions by using b-open sets. 2000 Mathematics Subject Classification. 54C05